Comparison of blood lactate in equestrian athletes in training and competition - Liu, R.; Qi, J.; Li, X. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: Equestrian sports requires the coordination of the athlete and the horse, and involves energy expenditure as a function of the physiological demands. The purpose of this study was to compare the blood lactate levels associated with training and competation. Methods Subjects consisted of 11 members from four representative teams participating in the 2006 National Equestrian Championships. The blood lactate concentration were tested by using a blood lactate Tester (Kyoto 1790) 2 minutes before and after training and competition. Data was analyzed using the statistical software SPSS13.0 for statistical analysis. Results From the blood lactate concentration of the equestrian athletes in the three races at 2 minutes before and 2 minutes after the competition several findings emerged. The blood lactate results were relatively higher after competition, which might relate with the athlete`s psychological and physiological responses. The average values of blood lactate concentration of athletes before and after competition were much higher than the average values in pre-training and post-training. The differences between the lactate levels in training compared with competition were statistically significant. The differences between training and competition lactate levels six minutes after competition/training were not statistically significant. Conclusions These findings suggest that training sessions are not preparing equestrian athletes for the anaerobic conditions of competition. Reforms in training efforts may help to accommodate this situation and better simulate the demands of actual competition.